Radiological and Histomorphometric Outcomes of Homologous Bone Graft in Postextractive Implant Sites: A 6-Year Retrospective Analysis. Issue 5 (October 2019) - Baldi, Domenico; Pesce, Paolo; Musante, Bruno; Pera, Francesco; Fulcheri, Ezio; Romano, Filomena; Menini, Maria
Abstract : Objectives: The aim was to investigate the in vivo efficacy of a cancellous particulate allograft bone in the regeneration of postextractive atrophic sites. Material and Methods: Ten patients were selected, and after a minimally invasive extraction of the teeth (T0), a cone beam computed tomography was performed (T1). Seven days after extraction, Puros cancellous particulate homologous graft was inserted into the elected sites together with a membrane (T2). After 4 months, a cone beam computed tomography of the sites was performed (T3). After 5 months, samples of the regenerated sites were taken contextually to implant insertion (T4). The samples were histologically and histomorphometrically analyzed. Intraoral periapical radiographs were accomplished at T4 and at the 6-year follow-up appointment (T5). Results: The mean vertical bone augmentation was of 4.1 mm in the lower jaw and of 3.35 mm in the maxilla at T3 appointment. The mean horizontal bone augmentation in the lower jaw was 2.02 and 2.15 mm in the maxilla. At T4, the mean total bone was 60.01% and the mature bone was 98.41. At the 6-year follow-up visit, the mean periimplant bone resorption was 0.14 mm (range 0–0.5 mm). Conclusions: Cancellous particulate allograft bone demonstrated excellent bone regeneration behavior both in terms of quantity and quality, and stable results over a 6-year period. Clinical Relevance: Cancellous allograft bone can be successfully used to regenerate atrophic sites.